2006
DOI: 10.1007/s10973-005-7354-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, spectral and AFM studies of calcium silicate hydrate-polymer nanocomposite material

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The weight loss as a function of temperature showed a pattern similar to that reported in the literature for C-S-H [27,28]. The morphological examination of the particles precipitated showed that it consisted of 15-10 nm particles regardless of the pH investigated, as may be seen from the SEM pictures shown in figure 11.…”
Section: Table 2 Precipitation Of C-s-h From Aqueous Supersaturated Ssupporting
confidence: 83%
“…The weight loss as a function of temperature showed a pattern similar to that reported in the literature for C-S-H [27,28]. The morphological examination of the particles precipitated showed that it consisted of 15-10 nm particles regardless of the pH investigated, as may be seen from the SEM pictures shown in figure 11.…”
Section: Table 2 Precipitation Of C-s-h From Aqueous Supersaturated Ssupporting
confidence: 83%
“…The first C-S-H/polymer nanocomposites were successfully synthesized by Matsuyama and Young [3][4][5][6][7], followed by Mojumdar and Raki [8,9], Mojumdar et al [10] and Beaudoin et al [2]. The authors tested cationic (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, λ эксп for PVA is reported to be 0.20 W/(m K) [43] and 0.1063 W/(m K) [44]. The thermal conductivity correlation diagram is presented in Fig.…”
Section: Thermal Conductivitymentioning
confidence: 99%